Advances in nuclear architecture - Adams, Niall M.; Freemont,Paul S.; SpringerLink (Online service). (Dordrecht Springer, 2011)
This book provides a snapshot of the state-of-the art in the study of mammalian cell nuclear architecture, and features a diverse range of chapters written by top researchers. A key aspect is an emphasis on precise and repeatable quantitative analysis and simulation in addition to the more familiar biological perspective. The fusion of such material frames the future of the discipline. Quantitative contributions stress reproducible and robust 3D analysis, using a variety of tools ranging from point pattern analysis to shape registration methods. Biological insights include the role of nuclear subdomains in cancer, nuclear molecular motors, and a holistic view of gene transcription.
Foreword -- Nuclear subdomains and cancer, Kendra L. Cann, Sui Huang and Graham Dellaire -- Spatial point process analysis of Promyelocytic Leukemia nuclear bodies, Philip P. Umande and David A. Stephens -- Quantitative approaches to nuclear architecture analysis and modeling, D. Hübschmann, N. Kepper, C. Cremer and G. Kreth -- Statistical shape theory and registration methods for analyzing the 3D architecture of chromatin in interphase cell nuclei, Siwei Yang, Doris Illner, Kathrin Teller, Irina Solovei, Roel van Driel, Boris Joffe, Thomas Cremer, Roland Eils, Karl Rohr -- Nuclear molecular motors for active, directed chromatin movement in interphase nuclei, Joanna M. Bridger and Ishita S. Mehta -- Methodology for quantitative analysis of 3-D nuclear architecture, Richard A. Russell, Niall. M. Adams, David A. Stephens, Elizabeth Batty, Kirsten Jensen and Paul S. Freemont -- Thinking holistically about gene transcription, Dean A. Jackson -- Index.
Electronic reproduction.
Keywords: Cell nuclei; Cytology; Electronic books